Re: Andrea Necchi, Félix Guerrero-Ramos, Paul L. Crispen, et al. Gemcitabine Intravesical System plus Cetrelimab or Cetrelimab Alone as Neoadjuvant Therapy in Patients with MIBC: Primary Analysis and Biomarker Results of SunRISe-4. J Clin Oncol. In press. https://doi.org/10.1200/JCO-25-02382 - Giuseppe Di Lorenzo; Carlo Buonerba (European Urology Oncology, 2026)
PURPOSE: EA1181 (ClinicalTrials.gov identifier: NCT04266249) is a single-arm trial evaluating neoadjuvant taxane, trastuzumab, and pertuzumab (THP) in patients with clinical stage II/IIIa human epidermal growth factor receptor 2 (HER2)-positive breast cancer. This report focuses on the secondary end points of pathologic complete response (pCR) rates and associated factors. The primary end point-3-year recurrence-free survival among patients achieving a pCR (ypT0/Tis, ypN0)-will be reported when data mature. METHODS: Patients received four cycles of trastuzumab and pertuzumab (HP) with either once per week paclitaxel (12 weeks) or docetaxel (every 3 weeks for four cycles), followed by surgery. Clinicopathologic characteristics were assessed in all patients. The HER2DX pCR score was determined using diagnostic biopsy samples in a representative subset. Logistic regression models identified factors associated with pCR. RESULTS: A total of 2,175 patients were enrolled (781 HER2+/estrogen receptor‑negative [ER-]; 1,394 HER2+/ER+). Of 2,141 patients who initiated THP, the overall pCR rate was 43.8%: 63.7% in HER2+/ER- and 32.4% in HER2+/ER+ tumors. Higher pCR rates were observed in tumors that were ER-negative or low ER expressing, progesterone receptor-negative or low expressing, HER2 immunohistochemistry (IHC) 3+, and in patients treated with once per week paclitaxel. T3 disease was associated with a lower pCR rate in HER2+/ER- tumors; otherwise, tumor (T) and nodal (N) stage did not significantly affect pCR. Among 569 patients assessed for HER2DX pCR scores, a high score was independently associated with higher pCR rates, after adjustment for clinicopathologic variables. CONCLUSION: Neoadjuvant THP achieved pCR in nearly two-thirds of patients with HER2+/ER- and one third with HER2+/ER+ breast cancer. Low hormone receptor expression, HER2 IHC 3+ status, once per week paclitaxel use, and a high HER2DX pCR score were independent predictors of pCR. These findings should help optimize risk stratification and treatment personalization for patients with HER2-positive breast cancer.